2018
DOI: 10.1038/s41598-018-32345-x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Studies on the Basic Transmission Properties of Electromagnetic Waves in Softmaterial Waveguides

Abstract: Conventional waveguides are usually made of metallic materials, and they are effective pathways for the transmission of electromagnetic waves. A “Softmaterial waveguide”, by contrast, is supposed to be made of dielectric material and ionic fluids. In this work, by means of both experiment and computational simulation we examined one kind of softmaterial waveguide, which has the configuration of ionic fluids filled in and out of a dielectric tube. We investigated configurations with varied parameters, i.e., tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 42 publications
(44 reference statements)
2
25
0
Order By: Relevance
“…In relation to this, further considerations can be made. The model of electromagnetic radiation coming from the node we recently proposed 19 and that one concerning the optical transmission through a myelin waveguide, previously described by Kumar and other authors [13][14][15][16]19 , are consistent with each other and with our experimental results and can be considered as a more comprehensive model, describing the whole sequence of generation and transmission of photons, in the node and through the myelin respectively. However, hypotheses describing how photons act when they reach the next node are still missing and deserve further research 13,19 .…”
Section: Photonic Radiation Detectedsupporting
confidence: 89%
See 1 more Smart Citation
“…In relation to this, further considerations can be made. The model of electromagnetic radiation coming from the node we recently proposed 19 and that one concerning the optical transmission through a myelin waveguide, previously described by Kumar and other authors [13][14][15][16]19 , are consistent with each other and with our experimental results and can be considered as a more comprehensive model, describing the whole sequence of generation and transmission of photons, in the node and through the myelin respectively. However, hypotheses describing how photons act when they reach the next node are still missing and deserve further research 13,19 .…”
Section: Photonic Radiation Detectedsupporting
confidence: 89%
“…Liu et al reported myelin sheath as a way for dramatic speed enhancement of signal propagation in nerves in the THz-infrared range 15 . Jingjing Xu et al mimicked the myelin sheath structure in myelinated axons 16 . They showed a clear confinement effect for the energy flux of transmitting electromagnetic waves inside a dielectric tube, strongly supporting the model of soft material waveguide.…”
mentioning
confidence: 99%
“…This results in an attenuated field strength when the pulsed signal arrives at the next signal source (20,17,19,21). This model explains well the highly overlapped successive action potentials as shown in Figure 1.…”
Section: Origin Of Signal Delay At Ranvier Nodessupporting
confidence: 53%
“…The distance between two neighboring signal sources, i.e., Ranvier nodes, is as long as several millimeters, thus much longer than the Debye length (about several nanometers) of ions in an electrolyte solution resulting from screen effect (16). The electromagnetic soliton-like model states that the neural signals are electromagnetic pulses generated by the transmembrane transient ion current, and they propagate via the naturally formed softmaterial dielectric waveguides with the structure of "intracellular fluidlipid membrane -extracellular fluid" (17)(18)(19). Both experiments and simulations showed the electromagnetic pulse signal has limited transmission efficiency when propagating via the softmaterial waveguide pathway.…”
Section: Origin Of Signal Delay At Ranvier Nodesmentioning
confidence: 99%
See 1 more Smart Citation